2011
DOI: 10.1002/ccd.22917
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary perfusion scans following transcatheter patent ductus arteriosus closure using the Amplatzer devices

Abstract: PDA closure with Amplatzer family of devices is associated with a relatively significant risk of decreased perfusion to the left lung, mostly mild abnormalities. Comparison with catheterization and echocardiographic measurements showed lack of correlation with LPRS findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 84 publications
0
8
0
1
Order By: Relevance
“…However, the incidence and severity of LPA stenosis may be underestimated because flow diversion to the right lung may prevent flow acceleration to the LPA. Indeed studies using scintigraphic perfusion imaging consistently showed evidence of decreased perfusion to the left lung after PDA occlusion with different devices and coils, which does not correlate with pressure measurements or echocardiographic findings . The clinical impact of these findings in the long term is unknown.…”
Section: Discussionmentioning
confidence: 97%
“…However, the incidence and severity of LPA stenosis may be underestimated because flow diversion to the right lung may prevent flow acceleration to the LPA. Indeed studies using scintigraphic perfusion imaging consistently showed evidence of decreased perfusion to the left lung after PDA occlusion with different devices and coils, which does not correlate with pressure measurements or echocardiographic findings . The clinical impact of these findings in the long term is unknown.…”
Section: Discussionmentioning
confidence: 97%
“…This raise our concerns about the excessive length of this device when dealing with large PDA in small infants with an infrequently but real risk to occlude the left pulmonary artery take off with the device proximal disc. Recently, a report was published on the long‐term pulmonary blood flow in patients who underwent PDA device closure with the ADO devices, suggesting this would not be a problem exclusively related to the AVP II device but related to the procedure itself when using devices for PDA closure. This complication seems to be anyway unusual and was reported to resolve on its own in the majority of cases, therefore, it is not contraindicated to use it for closure of large PDAs in small infants.…”
Section: Discussionmentioning
confidence: 99%
“…The experienced echocardiographer is able to determine precisely the location of the occluder. During the echo imaging we are able to estimate the flow in the aorta and in both pulmonary arteries in order to be sure that none of the vessels (especially the left pulmonary artery) are narrowed [6]. An additional advantage of our method is the reduction of the volume of contrast medium.…”
Section: Discussionmentioning
confidence: 99%